Diseño Organizacional para la cooperativa de producción industrial "Abacá Ecuador". - Moreira Alvarado, Jessica Leonor (2014)
The investigation consisted on Designing the Organic one functional for the Cooperative of Industrial Production "Abaca Ecuador", with the main office that is located in the city of I Remove and its storing centers in the County of Sacred Domingo of the Tsachilas whose purpose is to produce abaca fiber, dedicated to the international market. The area is characterized by a climate humid subtropical type, with temperature of 22,5° C, annual half precipitation of 2900 mm and a relative humidity of 90%. he thought about as objectives: To carry out a diagnosis of the current situation of the cooperative, to Elaborate the proposal of Design-organic functional of the cooperative. Information was obtained by means of interviews and surveys that then were processed by means of statistical techniques of distribution of frequencies, the interpretation of the information allowed to determine the administrative situation of the cooperative, on the base of which the proposal was formulated, to establish the structure of the flowchart of the cooperative. Of the analysis and interpretation of the results you concludes: The cooperative doesn't have a formal organizational structure, for what exists recharge of functions that they take to a series of annoyances, it is also observed duplicity of functions generating works descoordinadas that take to unconcluded processes, one can say that, the abilities and dexterities managed by the office workers of the directive one have not been enough to reach the innovation that favors the growth of the cooperative in the production processes and commercialization, The lack of a manual of functions delineated for each unit and position that the members of the directive one integrate, most of the personnel doesn't have an acceptable academic level and they are not adjusted to the profile of the position. It is required to motivate the partners of the Cooperative that it is in decrecimiento due to the lack of technical consultantship in the production area, and dissatisfaction of the prices, it is necessary also to implement the organizational culture that will take to the administration of the cooperative to look for to solve with creativity from their functions.